CAR-SPLASH identifies nascent pre-mRNA structures implicated in kinetic coupling and alternative splicing - Hossein Shenasa; Nova Fong; Benjamin Erickson; Ira A. Iosub; Jernej Ule; David L. Bentley (Proceedings of the National Academy of Sciences, 2025)
Pre-mRNA splicing is kinetically coupled to transcription as shown by the widespread effects of transcription speed on alternative splicing (AS) outcomes. The molecular basis for such kinetic coupling is incompletely understood, but one potential mechanism is through elongation rate–dependent alternative folding pathways of the nascent pre-messenger RNA (pre-mRNA). To search for RNA structures in nascent pre-mRNA, we modified Sequencing of Psoralen Crosslinked, Ligated And Selected Hybrids (SPLASH) [J. G. Ashley Aw et al. , Mol. Cell 62 , 603–617 (2016)] for use with C hromatin A ssociated R NA. We applied this method called Chromatin Associated RNA (CAR)-SPLASH to cells expressing wild-type and slow mutant RNA polymerase II and identified >3,000 intramolecular RNA duplexes of which >400 are proximal to splice sites. Antisense oligonucleotide (ASO) disruption of several such duplexes that sequester splice sites has a major impact on AS outcomes, even though the ASOs do not directly disrupt splice sites. ASO disruption of these regulatory elements that we designate “RNA kinetic switches” modified AS of NISCH Exon 18, GAK Exon 7, and MEGF8 Exon 14 in a way that depends on the rate of transcription elongation. We propose that these switches mediate kinetic coupling via the effects of transcription speed on folding of nascent RNA structures that modulate AS and that many nascent RNA structures can thereby serve as targets for splice-modifying ASOs.